2016
DOI: 10.1016/j.bonr.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Combined aerobic and resistance training improves bone health of female cancer survivors

Abstract: IntroductionCancer pathogenesis and resulting treatment may lead to bone loss and poor skeletal health in survivorship. The purpose of this investigation was to evaluate the influence of 26 weeks of combined aerobic and resistance-training (CART) exercise on bone mineral density (BMD) in a multi-racial sample of female cancer survivors.MethodsTwenty-six female cancer survivors volunteered to undergo CART for 1 h/day, 3 days/week, for 26 weeks. The Improving Physical Activity After Cancer Treatment (IMPAACT) Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 43 publications
1
33
0
1
Order By: Relevance
“…Based on the variables that improved, our hypothesis was partially affirmed. Pre-post increases to left calcaneal BMC and BMD far exceed gains seen previously and may be due to a significant decline in bone resorption [2,19,58]. It is important to explain why our BMC and BMD results 1): yielded greater gains than other studies, and 2): were confined to the calcaneus.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Based on the variables that improved, our hypothesis was partially affirmed. Pre-post increases to left calcaneal BMC and BMD far exceed gains seen previously and may be due to a significant decline in bone resorption [2,19,58]. It is important to explain why our BMC and BMD results 1): yielded greater gains than other studies, and 2): were confined to the calcaneus.…”
Section: Discussionmentioning
confidence: 47%
“…This led some to imply power train-ing, with its high movement rates and impact forces, was better for osteogenesis [14,16,24,33]. A combined 26-week aerobic and resistive exercise intervention produced modest ( + 1.7-2.5 %) BMD gains in female cancer survivors [2]. Impact forces from tennis (averaged 14.3 years of play) led to dominant arm muscle volume ( + 9.7 %) and BMC ( + 13.5 %) gains versus the non-dominant arm [18].…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal disorders are common in diabetic patients, and many researchers have found that the patients had reduced bone mineral content (24,25), deranged calcium and phosphate levels, and altered bone metabolism (26,27). While it has been proven that aerobic and resistance training improves bone health (28,29), there are only a few studies that have reported the effects of weight-bearing treadmill running on diabetes-induced bone loss. In accordance with the previous studies (30-32), we found that weight-bearing treadmill treatment reduced STZ-induced blood glucose, and increased STZ-induced blood insulin, weight mass, muscle mass, bone mass, and grip strength.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance and aerobic exercise training have been shown to preserve or improve bone density in cancer survivors and patients actively undergoing hormone therapy . Twenty‐six weeks of combined aerobic and resistance training has shown benefit for female cancer survivors in improved spine, hip, and whole body bone mineral density (BMD), but these results were not stratified by type of cancer or cancer therapy during primary tumor treatment . In another study, again not stratified by tumor type or treatment, 24 months of strength and weight training showed improved balance and muscle strength in breast cancer survivors .…”
Section: Exercise and Nutritional Interventionsmentioning
confidence: 99%